The Influence of Market Orientation, Technology Orientation and Entrepreneurial Orientation on Business Performance - Derry Pujianto; Hendy Tannady (Jurnal Multidisiplin Madani, 2023)
The economic growth of the creative industry in the coffee beverage sector has expanded due to Indonesia's rapid expansion of the food and beverage sector, particularly coffee outlets, however one coffee shop, specifically one in the Tangerang region, has dropped. This phenomena may be understood in terms of business performance, market orientation, technology orientation, and entrepreneurial orientation. This study's goal was to identify and evaluate how market orientation, technological orientation, and entrepreneurial orientation affect business performance. An online survey using a quantitative methodology is used in this study. A questionnaire that has previously undergone validity and reliability testing before being deemed valid was employed in the data gathering procedure. 120 respondents who were selected for the study's sample utilizing the non-probability sampling technique and judgmental sampling approach. In this work, multiple linear regression tests were used as the analytical method. According to the findings, Market Orientation, Technology Orientation, and Entrepreneurial Orientation all have a partial and simultaneous beneficial impact on Business Performance